Predictive technology and natural hazards: risk for Australian planning authorities?. Issue 1 (11th April 2016) - Stickley, Amanda; Christensen, Sharon; Duncan, W.D.; Buchbach, Jacinta
Abstract : Purpose: The purpose of this paper is to examine whether the improvements in technology that enhance community understanding of the frequency and severity of natural hazards also increased the risk of potential liability of planning authorities in negligence. In Australia, the National Strategy imposes a resilience-based approach to disaster management and stresses that responsible land-use planning can reduce or prevent the impact of natural hazards upon communities. Design/methodology/approach: This paper analyses how the principles of negligence allocate responsibility for loss suffered by a landowner in a hazard-prone area between the landowner and local government. Findings: The analysis in this paper concludes that despite being able to establish a causal link between the loss suffered by a landowner and the approval of a local authority to build in a hazard-prone area, it would be in the rarest of circumstances that a negligence action may be proven. Research limitations/implications: The focus of this paper is on planning policies and land development, not on the negligent provision of advice or information by the local authority. Practical implications: This paper identifies the issues a landowner may face when seeking compensation from a local authority for loss suffered because of the occurrence of a natural hazard known or predicted to be possible in the area. Originality/value: The paper establishes that as risk managers, local authorities must place reliance upon scientific modelling and predictive technology when determining planning processes to fulfil their responsibilities under the National Strategy and to limit any possible liability in negligence.